Treatment of ibuprofen intoxication in a dog via therapeutic plasma exchange. Issue 4 (8th May 2017) - Walton, Stuart; Ryan, Kirk A.; Davis, Jennifer L.; Acierno, Mark
Abstract: Objective: To describe the treatment of ibuprofen intoxication with therapeutic plasma exchange in a dog (TPE). Summary: A 13‐year‐old male neutered mixed breed dog presented after ingesting approximately 200 mg/kg of ibuprofen. Treatment consisted of supportive medical therapy with IV fluids, gastrointestinal protectants, antiemetics and prostaglandin analogs, and TPE. A cycle of TPE was performed over 180 minutes, achieving 1.5 plasma volume exchanges. During therapy, heparinized blood and effluent samples were collected. Ibuprofen concentrations were determined in the samples by high‐pressure liquid chromatography. Post TPE, the dog was continued on supportive medical therapy and was discharged 96 hours after the overdose. New or Unique Information: This report describes the use of TPE as an adjunct for ibuprofen intoxication. An 85% reduction in plasma ibuprofen concentration occurred and recovery from a potentially lethal ingestion of ibuprofen was achieved with TPE and supportive care. TPE should be considered when presented with acute ibuprofen intoxication due to the rapid and efficacious nature of therapy.